Corporate Compliance with ESG (Environmental, Social, and Governance): Perspectives on Business Law and Good Corporate Governance (GCG) - polontoh, Herry m; Kadir, Taqyuddin (Ipso Jure, 2025)
This study examines the urgency of integrating Environmental, Social, and Governance (ESG) principles into Indonesia's business law framework in response to global demands for sustainable corporate practices. Through a normative juridical approach, this study analyzes the disharmony of national regulations, especially between Law No. 40 of 2007 concerning Limited Liability Companies, Law No. 32 of 2009 concerning Environmental Protection and Management, and sectoral regulations from the OJK such as POJK No. 51/POJK.03/2017. The results of the study show that although ESG principles are beginning to be accommodated in some legal instruments, they are still administrative, sectoral, and do not have a strong binding force judicially. This has an impact on weak corporate accountability in carrying out environmental and social responsibility as part of Good Corporate Governance (GCG). This research emphasizes the importance of ESG codification as a positive legal norm that can be enforced through the supervision and accountability mechanism of the board of directors. Comparative studies with practices in the European Union and OECD show that the successful implementation of ESG is highly dependent on the existence of prescriptive norms and integrated monitoring systems. Therefore, the reformulation of Indonesian corporate law is crucial to realize inclusive, sustainable, and accountable business governance